2017
DOI: 10.1016/j.cptl.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Saudi undergraduate pharmacy students on pharmacovigilance and adverse drug reaction reporting: A National Survey

Abstract: Objective: To evaluate Saudi undergraduate pharmacy students' knowledge, attitude and readiness towards pharmacovigilance and reporting of adverse drug reactions (ADRs). Methods:A cross-sectional survey was conducted between January 15, 2016 and February 18, 2016 using a structured, validated and pilot-tested questionnaire among senior (year 4, 5 and 6) undergraduate pharmacy students enrolled at a governmental or private university/college. Students completed an online 27-item questionnaire developed using Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
8
1
Order By: Relevance
“…This is an important concept that needs to be acknowledged by healthcare students in order to know how and where to report an ADR. The study findings showed that only one-third of pharmacy students knew that SFDA is the governmental monitoring agency for adverse drug reactions in Saudi Arabia which is lower than the rate reported by Alkayyal N et al [18]. The present study revealed that about onethird of pharmacy students reported that the topic of PV is well covered in their curriculum, which is lower (55.6%) than the study done by Rajiah et al, among pharmacy students in Kuala Lumpur [19].…”
Section: Discussioncontrasting
confidence: 69%
“…This is an important concept that needs to be acknowledged by healthcare students in order to know how and where to report an ADR. The study findings showed that only one-third of pharmacy students knew that SFDA is the governmental monitoring agency for adverse drug reactions in Saudi Arabia which is lower than the rate reported by Alkayyal N et al [18]. The present study revealed that about onethird of pharmacy students reported that the topic of PV is well covered in their curriculum, which is lower (55.6%) than the study done by Rajiah et al, among pharmacy students in Kuala Lumpur [19].…”
Section: Discussioncontrasting
confidence: 69%
“…Studies that evaluated pharmacovigilance knowledge, attitude or perception of healthcare students started to appear since 2011. The majority of the included studies involved pharmacy students [11][12][13][14][15][16][17][18][19], while few studies specifically focused on healthcare students [20][21][22], nursing students [23], and dental students [24,25]. The total number of included studies was twenty-nine, with sample sizes ranging from 30 to 874.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…Attitude towards pharmacovigilance and ADR reporting was measured using multiple-choice response options ranging from 2 to 5 questions [20,30], and using a 5-point Likert scale [16,24]. Although only a few studies evaluated attitude; it should be noted that some questions used were related to measuring the perception rather than attitude [16,22,26,31]. The most commonly asked question was about the willingness of students to report any ADR in their future practice (S3 Appendix).…”
Section: Pharmacovigilance Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve health care professionals’ awareness of the importance of pharmacovigilance and encourage them to report ADRs, several educational interventions have been proposed. At the student level, the majority of interventions were lectures [3436]. However, in the study by Schutte et al the students had an opportunity to assess real ADR reports and this kind of education offered students a valuable pharmacovigilance experience, which resulted in increased awareness of ADR reporting [37].…”
Section: Discussionmentioning
confidence: 99%